El comportamiento áulico y su incidencia en el bajo rendimiento académico de los estudiantes de sexto y séptimo año de la unidad educativa “francisco Martínez Aguirre” de la ciudad de Vinces, cantón Vinces, Provincia los Ríos - Burgos Sánchez, Rosa Valeria (2016)
This research deals with classroom behavior and its impact on low academic performance in order to contribute to an adequate family and educational environment in order to positively influence the academic level, strengthen the ties between parents, students and teachers within the community. Educational Unit Francisco Martinez Aguirre. We worked with a participatory strategy where teachers addressed many important subtopics in which the behavior of their students in and out of the school is enriched to enrich a positive academic performance, taking into account the developments and skills of students such as students Of our institution is primary education, the social environment that most directly affects them is the family. This research resulted in better academic performance and therefore a high academic level in the classroom and influences an improvement in interpersonal relationships and interpersonal relationships of students.